The intensity feedback system at Heidelberg Ion-Beam Therapy Centre - Schömers, Christian; Feldmeier, Eike; Naumann, Jakob; Panse, Ralf; Peters, Andreas; Haberer, Thomas (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2015)
At Heidelberg Ion-Beam Therapy Centre (HIT), more than 2500 tumour patients have been treated with charged particle beams since 2009 using the raster scanning method. The tumour is irradiated slice-by-slice, each slice corresponding to a different beam energy. For the particle dose of each raster point the pre-irradiation by more distal slices has to be considered. This leads to highly inhomogeneous dose distributions within one iso-energy slice. - - The particles are extracted from the synchrotron via transverse RF knock-out. A pure feed forward control cannot take into account fluence inhomogeneities or deal with intensity fluctuations. So far, - fluctuations have been counteracted by a reduced scanning velocity. - - We now added a feedback loop to the extraction system. The dose - monitoring ionisation chambers in front of the patient have been coupled to the extraction device in the synchrotron. Characterization and implementation of the intensity feedback system into the HIT facility is described here. By its implementation the treatment time has been reduced by 10% in average.
Gesehen am 09.07.2020